The Likely Impact of the Implementation of ASEAN Economic Community 2015 on Local Small And Medium Enterprises - Tulus T.H. Tambunan (International Journal of Small and Medium Enterprises and Business Sustainability, 2015)
This paper, as part of ongoing research activities by the Center for Industry, SME and Business Competition Studies, University of Trisakti (Indonesia), aims to assess the likely impact of the implementation of ASEAN Economic Community by the end of 2015on small and medium enterprises (SMEs) in ASEAN member states (AMSs). The key question that this paper tries to answer is the following: through what channels the AEC 2015 will affect local SMEs? Although the economic integration of ASEAN in the contextAEC 2015 is not only on trade but also on foreign direct investment (FDI), capital, production and human resource/skilled workers, the analysis in this paper focuses only on regional trade liberalization.